Posterior Interosseous Nerve Syndrome from Thermal Injury. (6th March 2014) - Singh, Vijay A.; Michael, Rami E.; Dinh, Duy-Bao P.; Bloom, Scott; Cooper, Michael
Abstract : Background . Due to anatomical proximity to bone, the radial nerve is the most frequently injured major nerve of the upper extremity, frequently secondary to fractures (Li et al. (2013)). We describe an incidence when a branch of the radial nerve is injured as a result of a thermal injury. Observation . Radial nerve injury can occur anywhere along the anatomical course with varied etiologies, but commonly related to trauma. The most frequent site is in the proximal forearm involving the posterior interosseous branch. However, problems can occur at the junction of the middle and proximal thirds of the humerus and wrist radially. When the radial nerve is injured by a burn, a new rehabilitation dynamic arises. Not only does one agonize about the return of nerve function but also fret about the skin grafts that replaced the devitalized tissue housing that compartment. Discussion . Although posterior interosseous nerve syndrome has been described in the context of many different etiologies, it has not previously been discussed in relation to burn injuries. In this case, not only did the patient's rehabilitation involve aggressive therapy for return of sensation and function of the arm, but also prevention of contracture normally seen in replacement of full thickness burns.